Strategies for comprehension : understanding information for classroom, homework and test success - Mintzer, Richard. 4 0 16; 5 (New York : Rosen Central, 2006)
Introduces a number of strategies designed to help in understanding information for use in class preparation, homework, and written exams.
Comprehending by converting, describing, and explaining information -- Comprehending by interpreting, paraphrasing, putting in order -- Comprehending by restating, retelling in your own words, and rewriting -- Comprehending by summarizing, tracing, and translating.
Includes bibliographical references (p. 42-45) and index.
7.8;5-8;5-8
Keywords: 2 -- 0; 6; Thought and thinking;Comprehension;Thought and thinking.;Comprehension.;Thought and thinking.;Comprehension. -- Juvenile literature.;Juvenile literature; 20; 2